Clinical manual for treatment of alcoholism and addictions - Mack, Avram H. (IG library, 2010)
The Clinical Manual for Treatment of Alcoholism and Addictions provides a concise overview of addiction treatment issues relevant to clinicians who are involved in the care of patients with substance use disorders.